2021
DOI: 10.1177/0886260521992158
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of Bystanders’ Intention to Help Cyberbullying Victims Among College Students: An Application of Theory of Planned Behavior

Abstract: The goal of the present study was to evaluate the Theory of Planned Behavior (TPB) as an explanation for bystanders’ intention to help cyberbullying victims among college students. Participants completed an online survey in which their intention, attitude, subjective norm, and perceived behavioral control toward helping cyberbullying victims were assessed. In addition to these traditional TPB variables, empathy toward cyberbullying victims and anticipated regret from not helping victims were included in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…Because sexual assault exists on a continuum (McMahon et al, 2015) and students have shown variation in their intentions based on the type of intervention assessed (Hoxmeier et al, 2015), health-behavior theories such as the TPB may differ in their utility for predicting bystander intervention intentions. Also, important to note is that while this study was focused specifically on TPB variables, other variables can add to the prediction of bystander intervention intention, including the perceived cost of intervening (Dovidio, 1984), RMA (McMahon, 2010), and empathy (Hayashi & Tahmasbi, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Because sexual assault exists on a continuum (McMahon et al, 2015) and students have shown variation in their intentions based on the type of intervention assessed (Hoxmeier et al, 2015), health-behavior theories such as the TPB may differ in their utility for predicting bystander intervention intentions. Also, important to note is that while this study was focused specifically on TPB variables, other variables can add to the prediction of bystander intervention intention, including the perceived cost of intervening (Dovidio, 1984), RMA (McMahon, 2010), and empathy (Hayashi & Tahmasbi, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cyberbullying and cybervictimisation prevalence rates are not only erratic across countries but also not reliable as theoretical dimensions are often ignored [ 35 ]. Other studies also confirm that TPB in the context of social media could be used for planning and designing appropriate interventions to reduce the prevalence of cyberbullying [ 36 ] and understanding bystanders’ intentions [ 37 ].…”
Section: Introductionmentioning
confidence: 90%
“…The TPB (Ajzen, 1985) and the TTM (Prochaska & DiClemente, 1983) are often used in tandem with the situational model to measure other constructs theorized to be related to bystander behavior. The TPB (Ajzen, 1985) evaluates how attitudinal beliefs, perceived behavioral control, and existing subjective norms impact one’s intention to engage in a particular behavior (Hayashi & Tahmasbi, 2021). Ajzen (1985) theorizes that these constructs are precursors to behavior, with more supportive attitudes, stronger beliefs in one’s ability to act, and perception of a more supportive context all leading to increased intent to intervene and, in turn, actual behavior (Banyard & Moynihan, 2011; Burn, 2009; McMahon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%